PENGARUH INTEGRASI ENVIRONMENTAL SOCIAL GOVERNANCE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PSYCHOLOGICAL SAFETY SEBAGAI MEDIATOR - Tri Yunicha; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
This study examines the effect of Environmental Social Governance (ESG) integration on Organizational Citizenship Behavior (OCB), with Psychological Safety serving as a mediating variable at PDAM Tirta Manna Bengkulu Selatan. A quantitative research design was employed in this study. The population comprised all employees of PDAM Tirta Manna Bengkulu Selatan, and a total of 77 respondents were selected using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using linear regression analysis, t-tests, coefficient of determination (R²), and mediation analysis using the Sobel test with the assistance of SPSS software. The findings reveal that ESG integration has a positive and statistically significant effect on Psychological Safety. Furthermore, ESG integration significantly influences OCB, and Psychological Safety also exerts a positive and significant effect on OCB. The mediation analysis demonstrates that Psychological Safety partially mediates the relationship between ESG integration and OCB. These results suggest that effective ESG implementation not only contributes to organizational sustainability but also fosters a psychologically safe work environment, which subsequently enhances employees’ voluntary and extra-role behaviors reflected in Organizational Citizenship Behavior. Keywords: Integration Environmental Social Governance, Organizational Citizenship Behavior, Psychological Safety